Use of biological and chemical molecules in regulating embryo implantation and endometrial receptivity. Issue 4 (29th November 2022) - Chen, Xian; Sun, Shu-Ya; Ng, Ernest Hung-Yu; Li, Raymond Hang-Wun; Yeung, William Shu-Biu; Lee, Kai-Fai
Abstract : This review summarizes the drugs and chemicals that may modulate embryo implantation. Non-hormonal molecules, including aspirin, improved endometrial blood flow, while low molecular weight heparin, vitamin E, sildenafil, and atosiban modulated the expression of endometrial genes. Hormonal factors, including human chorionic gonadotropin and growth hormones, can regulate the expression of endometrial receptivity markers. Other immunomodulatory molecules, including granulocyte colony-stimulating factor, peripheral blood mononuclear cells, autologous platelet-rich plasma, and intralipid and intravenous immunoglobulins, may improve implantation rate by modulating endometrial immune functions. Medicinal extracts of the Chinese herbs Paeonia lactiflora and Perilla frutescens increased the expression of leukemia inhibitory factors in endometrial epithelial cells. Recently, the use of the commercially available Library of Pharmacologically Active Compounds with a high-throughput screening method has provided an approach to screen for compounds that may potentially enhance or suppress embryo implantation. Whether these biomedical findings translate into clinical effects that enhance or suppress embryo implantation requires further investigation.